Most used instruments in the assessment of functionality in the elderly with dementia: a systematic review - Almeida, Mariana Luciano; Leite, Juliana Cerqueira; Avalhais, Aryanne Pereira Soares; Melo, Beatriz Rodrigues de Souza; Thomaz, Catia Cristina; Botan, Zilda Rezende Mota; Manzini, Carlene Souza Silva; Vale, Francisco Assis Carvalho (Journal of Health Care, 2016)
Introduction: With the growth of the elderly population, dementia emerges as one of the most striking consequences of chronic degenerative diseases on the functionality of the elderly. Objective: To describe the instruments used by most studies for the evaluation of functionality in the elderly with dementia. Materials and Methods: A systematic review was carried out of papers in Portuguese, English and Spanish that addressed this matter between the years 2009-2014 . The selected databases were: SciELO, LILACS, CAPES Theses Database, PubMed, Web of Science, PsycINFO and Scopus. For the process of identifying and selecting the items found in the databases, we used the PRISMA method. Results: 62 different instruments that evaluate functionality in elderly people with dementia were identified, and in that sense it was necessary to highlight only the most frequent. The criteria for inclusion in the results was to only introduce the instruments found in more than four studies. Six instruments were identified among the most used, which corroborate those found in other recent systematic reviews. Conclusion: We found that Lawton and Brody Instrumental Activities of Daily Living Scale, Katz Index, Pfeffer Functional Activities Questionnaire, DAD, Barthel Index and ADCS-ADL are the most used instruments in evaluation of the functionality in elderly patients with dementia.
Keywords: Assessment; daily activities; dementia; elderly.